Prognostic value of preoperative 18F-FDG PET/CT in papillary thyroid cancer patients with a high metastatic lymph node ratio: a multicenter retrospective cohort study. Issue 5 (May 2017) - Kwon, Seong Young; Choi, Eun Kyoung; Kong, Eun Jung; Chong, Ari; Ha, Jung-Min; Chun, Kyung Ah; Cho, Ihn Ho; Bom, Hee-Seung; Min, Jung-Joon; Kim, Jahae; Song, Ho-Chun; O, Joo Hyun; et al.
Abstract : Objective: Metastatic lymph node ratio (MLNR) is a known significant predictor of disease-free survival in differentiated thyroid cancer. The authors investigated the ability of preoperative fluorine-18 fluorodeoxyglucose ( 18 F-FDG) PET/CT to predict recurrence after surgery with radioactive iodine therapy considering MLNR. Patients and methods: A total of 274 patients who underwent preoperative PET/CT and surgery with radioactive iodine therapy were enrolled. The tumor-to-liver uptake ratio on PET/CT was calculated by dividing the maximum standardized uptake value of a primary lesion by the mean standardized uptake value of the normal liver. High 18 F-FDG uptake was defined as tumor-to-liver uptake ratio more than the median cutoff value (2.1). MLNR was calculated by dividing the number of metastatic lymph nodes (LNs) by the number of cervical LNs removed. A high MLNR was also defined as one more than a threshold value (0.4), identified by plotting Kaplan–Meier survival curves and comparing them using the log-rank test. The prognostic significances of clinicopathologic variables were analyzed. Results: Fifteen (5.5%) patients developed recurrence in the thyroid bed or in cervical LNs. Cox regression analysis showed that a high MLNR was significantly associated with a worse disease-free survival (odds ratio 6.95; 95% confidence interval: 2.36–20.47; P <0.001). A subgroup analysis of 70 patients with a high MLNR showed that only high 18 F-FDG uptake was significantly associated with a worse disease-free survival (odds ratio 5.77; 95% confidence interval: 1.22–27.16; P =0.027). Conclusion: High 18 F-FDG uptake of primary lesion on preoperative PET/CT has selective prognostic value according to the extent of metastatic LNs (MLNR>0.4).